Clinostomum marginatum infestation in Poecilia reticulata guppy collected in the Peruvian amazon and the identification of the species involved in its life cycle - Murrieta Morey, Germán Augusto (2025)
Poecilia reticulata (Peters, 1859), popularly known as the guppy, is a small fi sh commonly confined to the shallow edges of pools and streams and also found in heavily polluted water bodies. In natural and artificial environments, this fish species can be infected by a wide range of pathogens and parasites. In the present study, we reported for the first time in the Peruvian Amazon, the infestation of metacercariae of Clinostomum marginatum (Rudolphi, 1819) in the body of specimens of P. reticulata. Between May and June 2024, fifty specimens of P. reticulata were collected from an urban stream in the city of Iquitos, Loreto, Peru. Samples were collected at the “Laboratorio de Parasitolog.a y Sanidad Acuícola” from the “Instituto de Investigaciones de la Amazon.a Peruana” (IIAP) in Loreto, Peru. Metacercariae of C.marginatum were observed embedded in the muscle tissue of 100% of sampled guppies. The freshwater snail Pomacea maculata (Perry, 1810) was captured in the same stream as guppies, acting as the first intermediate host. Poecilia reticulata acts as the second intermediate host, while the striated heron Butorides striata (Linnaeus, 1758) was observed as the definitive host where the adult parasites feed and reproduce. This is the first record of C. marginatum parasitizing P. reticulata from the Peruvian Amazon.